2010
DOI: 10.1007/s00284-010-9761-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acrylamidase Isolated from a Newly Isolated Acrylamide-Utilizing Bacterium, Ralstonia eutropha AUM-01

Abstract: A mesophilic bacterium capable of utilizing acrylamide was isolated, AUM-01, from soil collected from leaf litter at Picnic Point on the UW-Madison campus. In minimal medium with acrylamide as the sole carbon and nitrogen source, a batch culture of AUM-01 completely converted 28.0 mM acrylamide to acrylic acid in 8 h and reached a cell density of 0.3 (A₆₀₀)). Afterward all the acrylic acid was degraded by 20 h with the cell density increasing to 1.9 (A₆₀₀). The acrylamide-utilizing bacterium was identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Ralstonia eutropha (Cha and Chambliss 2011) or Arthrobacter strains (Yamada et al 1979). The concentration of AMD that can be tolerated and degraded depends on the bacterial strain.…”
Section: Bio-degradation Of Acrylamidementioning
confidence: 99%
“…Ralstonia eutropha (Cha and Chambliss 2011) or Arthrobacter strains (Yamada et al 1979). The concentration of AMD that can be tolerated and degraded depends on the bacterial strain.…”
Section: Bio-degradation Of Acrylamidementioning
confidence: 99%
“…Another type of solidifying agent commonly used in microbial and molecular biology laboratories is acrylamide. Although microbes capable of acrylamide depolymerization have been reported (Cha and Chambliss 2011), they appear to be uncommon in nature. Previous reports have utilized acrylamide as an encapsulation matrix for E. coli, without loss of metabolic activity (Tosa et al 1974).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that Pseudomonas stutzeri shows an optimum growth at 440 mg l -1 acrylamide [19], while Ralstonia eutropha TDM-3 can utilize up to 780 mg l -1 acrylamide [17]. Ralstonia eutropha AUM-01, however, can utilize up to 1990 mg l -1 acrylamide as the sole carbon and nitrogen source [18]. Bacillus cereus strain DRY135 shows optimum growth at between 1000 and 2000 mg l -1 acrylamide [21].…”
Section: Discussionmentioning
confidence: 99%
“…Acrylamide degradation generally follows an acrylic acid intermediate formation and this is true in this yeast strain as well as in A. oryzae [25] and in other bacteria such as Pseudomonas stutzeri [17], Bacillus cereus strain DRY135 [21], Ralstonia eutropha AUM-01 [18] and Pseudomonas sp. strain DRYJ7 [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation